1992
DOI: 10.3758/bf03334113
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and explicit memory and response bias

Abstract: The influence of response bias on tests of implicit and explicit memory was assessed by using word-stem completion and recognition. During acquisition, subjects were presented either with a list of words unrelated to the task in the retrieval phase or with a list of words whose stems could be completed in only two ways (e.g. " appeal," "appear"). In the word-stem-completion retrieval phase, the subjects, who were given either explicit or implicit memory instructions, were asked to complete these stems. Retriev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
1995
1995

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…On the other hand, the item-based correlations between all three measures were significantly positive. The large correlation between^loid andv4 new confirms the fact that baseline item characteristics are a dominant source of variance in stem completion (see also, Deutsch, 1992;Hintzman & Hartry, 1990;Ostergaard, 1992). More important, the positive correlation of R o \ a with both/l new and^4 o id represents a violation of the assumption that R and A are independent.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…On the other hand, the item-based correlations between all three measures were significantly positive. The large correlation between^loid andv4 new confirms the fact that baseline item characteristics are a dominant source of variance in stem completion (see also, Deutsch, 1992;Hintzman & Hartry, 1990;Ostergaard, 1992). More important, the positive correlation of R o \ a with both/l new and^4 o id represents a violation of the assumption that R and A are independent.…”
Section: Resultsmentioning
confidence: 71%
“…Hintzman and Hartry (1990) found that priming accounted for just over 5% of the variance in completion rates, whereas a large percentage of variance was attributable to characteristics of the cues in word-fragment completion, which is similar to stem completion (Roediger, Weldon, Stadler, & Riegler, 1992). In general, performance on an indirect test such as stem or fragment completion may only slightly be mediated by priming when participants can successfully complete many stems without previous study (see also Deutsch, 1992; Ostergaard, 1992). Thus, correlations arising from inherent differences among items are particularly likely in a task such as stem completion.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, this line of argument extends to manipulations other than generation or LoP. The general point is that the strategy advocated in the retrieval intentionality criterion—equating cues and varying only instructions across tests—may not produce only differences in retrieval orientation (implicit or explicit) but instead produce only differences in response criterion (Deutsch, 1992; Reingold & Merikle, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions, an indirect test is assumed to be process pure (i.e., uncontaminated) when it does not respond, or when it responds differentially, to a variable that affects performance on the direct test. Two problems for this method are (a) potential differences in sensitivity or response criteria across the two tests (Deutsch, 1992; Reingold & Merikle, 1991) and (b) the evidence that unconscious processes contribute to performance on direct tests of memory (Jacoby, Toth, & Yonelinas, 1993). These findings suggest that it may not always be appropriate to use performance on a direct test as a benchmark or ideal against which to compare performance on an indirect test.…”
Section: Conceptual Automaticity and The Problem Of Conscious Contami...mentioning
confidence: 99%